Removal of heavy metals from mining wastewater by using prepared coco peat activated carbon as adsorbent - Keoduangchai Keokhamphui (College of Engineering, University of the Philippines Diliman, 2011)
Removal of heavy metals from wastewater is a challenge to environmental engineers due to the high concentration of metal contaminants such as lead, copper, cadmium, and arsenic. One method of removing these metals ions is the use of adsorption. This study determines the adsorptive capacity of the activated coco peat to remove Cu²+, Pb²+, Cd²+, and As²+ ions from aqueous solution. Coco peat was activated employing chemical activation, using ZnCI₂ and H₂SO₄ as chemical activating agents with impregnation ratio 3:1 (ZnCI₂: Coco Peat). Activated carbon from coco peat was found to have a high Brunauer-Emmett-Teller (BET) surface area of 2,121 m²/g and pore volume of 1.398 cm³/g. The products were also characterized by using thermo gravimetric (TG), Scanning Electron Microscopy (SEM), and Fourier Transform Infrared (FTIR) spectra. The adsorption experiments were obtained in batch reactor. various parameters such as contact time, initial metal concentrations, pH solution, adsorbent dosage, and temperature were varied to establish optimum conditions. The maximum adsorption capacity was observed at pH 6.0. The kinetics fitted well with pseudo-second order model. The adsorption isotherms fit the Langmuir and Freundlich models for Cu²+ and Pb²+. However, adsorption isotherm of Cd²+ fit the Freundlich model, and As³+ did not fit both Langmuir and Freundlich models. Thermodynamic parameters such as the standard free (ΔG⁰), enthalpy change (ΔH⁰), and entropy change (ΔH⁰) were determined. The adsorption capacity of the coco peat activated carbon was compared to that of the fresh coco peat and commercial activated carbon (Norit Activated Carbon). The study also evaluated and confirmed the adsorption of metals using Energy Dispersive Spectroscopy (EDS)image mapping and X-Ray Diffractometer (XRD) pattern. Activated coco peat was found to have high removal efficiency of Pb²+ and Cu²+ among heavy metals tested. The desorption studeis revealed that activated coco peat can be regenerated by using ).1HCL as dissolved solution. However, the 100% integrity of the original material could not be ascertained due to possible hydrolysis aided by the introduction of 0.1M HCI. Nevertheless, literatures show substantial hydrolysis only happening in high temperature conditions like that of 120⁰Ctemperature level.